2022
DOI: 10.3855/jidc.13881
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of hospitalized adults with COVID-19 in Nepal: a multicenter, prospective cohort study

Abstract: Introduction: There is limited data on clinical course and outcomes of hospitalized adults with COVID-19 in Nepal. Thus, it is imperative to characterize the features of this disease in the domestic context. Methodology: We identified all adult patients with laboratory-confirmed COVID-19 admitted to five different hospitals in Nepal from June 15 to July 15, 2020. We collected epidemiological, socio-cultural and clinicopathologic data, and stratified the patients based on their symptom status. Resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In 27 studies, SARS-CoV-2 positive patients were enrolled and followed up in the hospital setting. 27–53 Only 3 community/international traveler/repatriation screening studies 54–56 were included as those studies reported follow-up outcomes. In addition, 7 disease surveillance studies were included with follow-up outcomes presented in the publication 57–61 or correspondence with authors.…”
Section: Resultsmentioning
confidence: 99%
“…In 27 studies, SARS-CoV-2 positive patients were enrolled and followed up in the hospital setting. 27–53 Only 3 community/international traveler/repatriation screening studies 54–56 were included as those studies reported follow-up outcomes. In addition, 7 disease surveillance studies were included with follow-up outcomes presented in the publication 57–61 or correspondence with authors.…”
Section: Resultsmentioning
confidence: 99%
“…The severity of the disease and mortality due to COVID-19 may vary depending on the patient’s age, health status, presence of comorbidities, and regional availability of medical services. According to numerous studies, about 15% of patients infected with SARS-CoV-2 require hospitalisation, with approximately 5% requiring intensive care unit treatment [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%